Evaluasi Pembelajaran pada Mata Pelajaran Matematika: Antara Harapan dan Kenyataan di Kelas - Hasbi Hasidik; Nita Putri Utami (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to evaluate the implementation of evaluation and assessment in mathematics learning at MAN 1 Padang, focusing on the gap between the ideal expectations and the reality in the classroom. Using a descriptive qualitative approach and semi-structured interviews with mathematics teachers of grades 10, 11, and 12 conducted in May 2025, this study analyzes the evaluation practices, challenges encountered, and the alignment between expectations and actual practice. The results indicate that mathematics evaluation is still dominated by written tests that inadequately measure students' comprehensive abilities, while time constraints, conventional teaching methods, and low student participation remain significant obstacles. Therefore, it is necessary to develop more varied and authentic evaluation instruments and enhance teachers' capacity through training to make assessments more effective in supporting the achievement of comprehensive and sustainable mathematics learning objectives.